Effect of hydrothermal carbonization on heavy metals in swine manure: Speciation, bioavailability and environmental risk. (15th March 2019) - Lang, Qianqian; Chen, Mengjun; Guo, Yanchuan; Liu, Zhengang; Gai, Chao
Abstract: The speciation, bioavailability and environmental risk of heavy metals (HMs) in the hydrochar derived from hydrothermal carbonization (HTC) of swine manure were investigated in this study. The results indicated that the majority of HMs originally in swine manure were retained in the hydrochar by HTC, and CaO addition substantially reduced the HMs concentration in the hydrochar. HTC especially CaO assisted HTC significantly promoted the HMs transformation from the bioavailable fraction to the relatively stable fraction, and thus decreased their environmental risk in the hydrochar. Moreover, the Toxicity Characteristic Leaching Procedure and diethylenetriamine pentaacetic acid test revealed that the leachability and plant-bioavailability of HMs in swine manure were greatly declined by HTC especially for HTC with 15% CaO addition. The present study suggested that HTC was an effective disposal approach for swine manure from the perspective of HMs immobilization, especially for CaO assisted HTC. Graphical abstract: Image 1017 Highlights: The risk of HMs in the hydrochar from HTC of swine manure were studied. The majority of HMs were retained in the hydrochar by HTC. CaO assisted HTC decreased HMs concentration and immobilized HMs in the hydrochar. HTC especially with CaO addition reduced the leachable and plant-available HMs.